KEBIJAKAN PEMBERITAAN KANTOR BERITA ANTARA DI ERA KONVERGENSI MEDIA - Meti Nurhayati (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2021)
This research on the work of the ANTARA News Agency uses a qualitative research approach. The phenomenological method and using critical discourse analysis on news text framing, the study focused on how ANTARA framed its news in the Reformation era and media convergence (from 1998 to the present) by paying attention to news framing in the previous era (Old Order and New Order eras). to sharpen research. This study seeks to explore comprehensive information about how ANTARA's news framing was during the reform era and the era of media convergence, by paying attention to how the same policies in the previous government (the New Order era) sharpened the focus of the research. The results of the study indicate that press coverage, including ANTARA during the New Order era, followed the policies of the authorities, but also contributed to the creation of national stability and the establishment of the Unitary State of the Republic of Indonesia (NKRI) because it did not broadcast news on SARA issues. Meanwhile, during the reformation period, the nuances of the “national vision” or ideology of the mass media, including ANTARA, tended to diminish. In accordance with its historical role for the state, ANTARA in the future can and needs to carry out the function of press diplomacy in an effort to improve Indonesia's image in the international world. Meanwhile, ANTARA's true dedication and loyalty is not to the government (the rulers), but to the state, in this case the Unitary State of the Republic of Indonesia.